The primary percutaneous coronary intervention for acute anterior myocardial infarction in a middle-aged male patient with bilateral coronary artery to pulmonary artery fistulas - Altay, Servet (BMJ Case Rep, 2012)
A 38-year-old man admitted to emergency department with 2 h of typical substernal chest pain, shortness of breath and nausea. The ECG revealed sinus rhythm with a 3 mm ST elevation in precordial leads V1–V6. The coronary angiography revealed acute total occlusion in left anterior descending artery (LAD) with normal circumflex and right coronary artery (RCA) along with bilateral fistulas arising from the proximal LAD and ostial RCA draining into the main pulmonary artery. Therefore, primary percutaneous coronary intervention and bare metal stent implantation was performed to culprit LAD lesion. The electrocardiographically gated 64-slice multidetector-row CT showed two large, tortuous abnormal vessels which arose from the both ostial part of the RCA and LAD draining into the main pulmonary artery. We report an unusual case of bilateral coronary artery to pulmonary artery fistulas leading to acute anterior myocardial infarction in a middle-aged male patient.